2020
DOI: 10.3390/su12208702
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Increasing the Effectiveness of Learning by Using Active Methodologies

Abstract: One of the most important objectives of the Sustainable Development Goals (SDGs) is quality education, which is related to reducing school dropouts. To this end, the use of active learning methodologies improves the motivation, facilitating the learning process and, hence, reducing the dropouts. The present study proposes a methodological approach based on collaborative learning, titled: Presentation–Questions–Answers (PQA). The aim of the research is to determine whether the use of a collaborative learning me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In this way, all students are participants in the questions and have been able to demonstrate their acquired knowledge and the professors have only taken part in the resolution of the same when no student has been able to give a correct answer, thus playing professors a secondary role. This is in accordance with previous studies where an active role of students in the teaching‐learning process is recommended [17]. In consequence, it was concluded that it is possible to develop these simulators and that the collaborative attitude of professors affects their teaching [14].…”
Section: Resultssupporting
confidence: 89%
“…In this way, all students are participants in the questions and have been able to demonstrate their acquired knowledge and the professors have only taken part in the resolution of the same when no student has been able to give a correct answer, thus playing professors a secondary role. This is in accordance with previous studies where an active role of students in the teaching‐learning process is recommended [17]. In consequence, it was concluded that it is possible to develop these simulators and that the collaborative attitude of professors affects their teaching [14].…”
Section: Resultssupporting
confidence: 89%
“…Moreover, it coincides with the ethnomusicological perspective that conceives of music as a socio-cultural phenomenon that requires cooperation and coordination [ 54 ]. This perspective would also contribute to broadening the theoretical basis that justifies the use of active methodologies in the classroom as opposed to more traditional models focused on theory, technique, and individual learning [ 89 , 90 , 91 , 92 ]. In further research, it would be useful to study not only the greater or lesser use of music, but also the methodology implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Many of them at many different educational levels were unable to cope with the situation of increased stress and isolation [ 16 ], even abandoning their professional careers [ 17 ]. Other teachers coped with the situation by applying active and effective learning strategies in order to reduce the risk of increasing their stress and burnout [ 18 , 19 , 20 ]. These quick pedagogical decisions taken by teachers in the first moments of the confinement were very important in the subsequent distance teaching–learning process [ 21 ].…”
Section: Introductionmentioning
confidence: 99%